Contemporary Challenges and Prospects of Mediation in Contested Divorce Cases in Indonesia - Yangto; Sayehu; Nafan Tarihoran; Mustafa Ali Almagdub (Islamic Research Publiser, 2025)
Contested divorce cases in Indonesia have increased significantly over the past decade, revealing deep social and gender tensions within the contemporary Islamic family law system. Although mandatory mediation is regulated under Supreme Court Regulation (PERMA) No. 1 of 2016, its implementation remains largely ineffective and inconsistent. This raises critical questions: to what extent does mediation serve as a genuine conflict resolution mechanism rather than a formal procedural requirement? How effective is it in reducing litigation, ensuring justice, and what institutional and socio-cultural barriers limit its success? This study employs a combined meta-analysis and systematic review using PRISMA 2020 guidelines, examining 41 verified scientific articles, empirical reports, and case studies published between 2010 and 2024 from Scopus, PubMed, Mendeley, and ScienceDirect. The main findings indicate: 1) mediation success rates remain below 20%, particularly in cases involving domestic violence, financial disputes, and high emotional conflict; 2) institutional gaps, including undertrained mediators and the absence of standardized practices, contribute to procedural inconsistencies; 3) structural issues, such as gender imbalances and low public trust in non-litigation processes, further weaken the potential of mediation. Comparative analysis with Malaysia, Morocco, and Egypt shows that mediation is more effective when grounded in religious legitimacy, gender equality, and cultural sensitivity. This study contributes to the contemporary Islamic family law literature by providing a fiqh siyasah-based framework for evaluating mediation and offers practical guidance for judges, policymakers, and scholars to develop fair, sustainable, and culturally informed mediation policies in Indonesia.